The eye of God : a novel - Bemelmans, Ludwig, 1898-1962 (Viking Press, 1949)
The novel's theme is the love of a father for his son; and the moments that shine most brightly in it are the scenes in his native Tyrol. The simple life of the innkeeper Arbogast Tanneg, enjoying his pipe in front of the fire or hunting the chamois on the mountain, is invaded by big business in the form of winter 'sportlers,' who bring with them the whole crazy apparatus of resort hotels, worldly intrigue, rich bankers, and beautiful women of mystery.